Indigenous parents and child welfare: Mistrust, epistemic injustice, and training - Leckey, Robert; Schmieder-Gropen, Raphael; Nnebe, Chukwubuikem; Clouthier, Miriam (Social & Legal Studies, 2022)
The settler state's taking of Indigenous children into care disrupts their communities and continues destructive, assimilationist policies. This article presents the perceptions of lawyers, social workers and judges of how Indigenous parents experience child welfare in Quebec. Our participants characterized those experiences negatively. Barriers of language and culture as well as mistrust impede meaningful participation. Parents experience epistemic injustice, wronged in their capacity as knowers. Mistrust also hampers efforts to include Indigenous workers in the system. Emphasizing state workers’ ignorance of Indigenous family practices and the harms of settler colonialism, participants called for greater training. But critical literature on professional education signals the limits of such training to change institutions. Our findings reinforce the jurisdictional calls away from improving the system towards empowering Indigenous peoples to run services of child welfare. The patterns detected and theoretical resources used are relevant to researchers of other institutions that interact with vulnerable populations.
Keywords: 2000 à aujourd'hui; 2020-2029; amériques; approches et analyses; australie; canada; care; cours; cycles supérieurs; discipline; droit; enfants autochtones; fem9000; injustice; inégalités; nouvelle-zélande; océanie; politique assimilationniste; périodes historiques; racisme; régions géographiques; santé; science politique et droit; sciences humaines; sciences sociales; système colonial; systèmes d'oppressions; thématiques; violences; états coloniaux

Burn-out et travail social : Du changement aux résistances à l'épreuve - Ben Mrad, Fatih (L'Harmattan, 2017)
Le burn-out est devenu un sujet rebattu. Le sous-titre de ce livre traduit la volonté de l'auteur de s'intéresser à la manière dont certains professionnels sont affectés par leur situation, des points de vue physique, psychologique et social. Quels sont les changements personnels que les individus connaissent lorsqu'ils sont confrontés à l'expérience d'un burn-out et lorsqu'ils doivent déployer certaines de leurs ressources pour résister et faire face à leur situation ? A partir de ses observations, l'auteur propose de mieux considérer certains éléments minorés dans les travaux internationaux sur le sujet.
Keywords: 2000 à aujourd'hui; 2010-2019; cours; cycles supérieurs; discipline; europe; fem7000; périodes historiques; régions géographiques; santé; santé mentale; sciences humaines; sofia; thématiques; travail; travail social